Analysis of the influence of leadership on the motivation of employees in the tourism sector of the Republic of Serbia - Ace Milenkovski; Janovac Tatjana; Oliver Momčilović (UTMS Journal of Economics, 2023)
Motivation is a complex and dynamic factor that contributes to business success. Many factors influence the motivation of employees. The paper examines the influence of leadership on the motivation of employees in the tourism sector. The empirical research was conducted in September 2023. using an e-questionnaire on a sample of 270 employees in the tourism sector of the Republic of Serbia. The results obtained from empiricalstatistical research were processed using mathematical-statistical methods such as descriptive statistics, correlation analysis, regression analysis and ANOVA test. The research results indicate that the correlation between leadership and motivation is strong and positive (0.7998). Also, the results show that the coefficient of determination is 0.6396, which means that with 63.96% the dependent variable motivation (Q) can be explained by the independent variable leadership (P). The work is important from the aspect of providing guidelines to policy makers, owners and management of organizations in the tourism sector in order to increase the level of motivation among employees, which implies better performance and achieving business success.
Keywords: M12; O15; Z32; 330; motivation; leadership; performance; tourism sector